2009
DOI: 10.1038/nbt.1538
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial discovery in actinomycetes strains with mutations in RNA polymerase or ribosomal protein S12

Abstract: We show that selection of drug-resistant bacterial mutants allows the discovery of antibacterial compounds. Mutant strains of a soil-isolated Streptomyces species that does not produce antibacterials synthesize a previously unknown class of antibacterial, which we name piperidamycin. Overall, 6% of non-Streptomyces actinomycetes species and 43% of Streptomyces species that do not produce antibacterials are activated to produce them. The antibacterial-producing mutants all carried mutations in RNA polymerase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
186
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(193 citation statements)
references
References 15 publications
2
186
1
Order By: Relevance
“…The mechanism of action, however, remains to be clarified. The present method, together with other methods reported recently, 8,9,12,[22][23][24] may be useful for activating silent genes, eventually leading to the discovery of novel biologically active compounds. Figure 3 Comparative metabolic profiling of the culture extracts.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The mechanism of action, however, remains to be clarified. The present method, together with other methods reported recently, 8,9,12,[22][23][24] may be useful for activating silent genes, eventually leading to the discovery of novel biologically active compounds. Figure 3 Comparative metabolic profiling of the culture extracts.…”
Section: Resultsmentioning
confidence: 81%
“…12,17 The activation of silent genes by generating rpoB H437D or rpoB H437L mutations in Streptomyces sp. 631689 was attributed, at least in part, to the increased affinity of the mutant RNA polymerase for promoters.…”
Section: Effects Of Scandium and Lanthanum On Transcription Of Secondmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, different expression strains have been developed to facilitate gene cluster expression and metabolite detection. For instance, the model organism S. coelicolor has been genetically engineered in a manner that positively affects antibiotic production in general (by altered RNA polymerase and ribosome) (Hosaka et al ., 2009) and in addition alleviates the detection of antibiotic production (by inactivated active secondary metabolite gene clusters ( ∆act ∆red ∆cpk ∆cda )) (Gomez‐Escribano and Bibb, 2012). Heterologous expression of antibiotic gene clusters has been a challenge for a long time because cluster sizes can easily reach more than 100 kb, which makes them difficult to clone.…”
Section: Novel Approaches For Drug Discoverymentioning
confidence: 99%
“…This in turn revealed that the previously identified molecule pulvomycin inhibits the growth of several highly resistant pathogenic bacteria. It is our hope that screening engineered streptomycetes against both antibioticsensitive and -resistant target strains, along with innovations from other laboratories, 21 will help to fuel a much needed renaissance in antibacterial discovery.…”
Section: Discussionmentioning
confidence: 99%